Al-Dalālah al-Ramziyyah li al-Alfāẓ al-Zamāniyyah wa al-Makāniyyah fī Qaṣīdah “A‘rāf al-Ma‘ārif” li Bello Mustapha al-Mangārī (Dirāsah Ṣarfiyyah Dalāliyyah) - Yahya, Dahiru; Muhammad, Muhammad Gambo; Umar, Aishatu (Study Program of Arabic Language Teaching, 2026)
This study examines the symbolic significance of temporal and spatial expressions in the Sufi poem “A‘rāf al-Ma‘ārif” by Bello Mustafa Al-Mangari, adopting a morpho–semantic approach that reveals the transition of lexical items from their literal meanings to mystical, symbolic dimensions. The research identifies key temporal and spatial terms in the poem, analyzes their morphological structures, and explores their semantic functions within the spiritual narrative of the text. Findings indicate that space in the poem functions as a spiritual locus as reflected in references such as Durbal, Yarwa, Gwange, and the Sheikh’s House while time becomes a spiritual state rather than a physical measurement, as seen in terms like ages, feasts, time, and canopies of blessings. These expressions transcend their material meanings to symbolize Sufi stations and experiential states. The analysis further shows that morphological patterns especially noun forms of place, verbal nouns, and broken plurals enhance the density and depth of symbolic meaning. The study concludes that “A‘rāf al-Ma‘ārif” represents a rich model of Sufi symbolism in which time and place are reconfigured according to spiritual experience, demonstrating the poet’s skill in employing linguistic structures to construct an integrated mystical discourse.